Solusi Gizi Terjangkau untuk Mencegah Stunting di Desa Alangamba: Sosialisasi dan Demo Masak Nugget Lele - Tri Wahyu Yuliani; Labib Hidayat; Meiva Putri Rahmawati; Altafa Nabili Meilano; Fadila Putri Farkhani (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2025)
Stunting remains a health problem in Indonesia, including in Alangamba Village, Binangun District, Cilacap Regency, Central Java, where 10 out of 103 children experience stunting. One of the causes of stunting is the community's understanding of nutrition and childcare patterns are the main causes. This community service activity aims to increase community knowledge about stunting prevention and improve skills in processing nutritious food through socialization and catfish nugget cooking demonstrations. The activity methods include a pre-test, socialization of materials related to stunting, catfish nugget cooking demonstrations, and post-tests, with a total of 31 participants. The results of the SPSS analysis using the Wilcoxon test showed an increase in the average level of knowledge of participants from 7.03 to 8.43 and as many as 25 participants experienced an increase in knowledge after being given socialization. This activity proves that education can increase community understanding and knowledge about the importance of early stunting prevention and is able to provide solutions to fulfill children's nutritional needs through providing food with affordable local food ingredients.